1999
DOI: 10.1103/physrevlett.82.2824
|View full text |Cite
|
Sign up to set email alerts
|

Vortex String Formation in a 3D U(1) Temperature Quench

Abstract: We report the first large scale numerical study of the dynamics of the second order phase transition of a U(1) $\lambda \phi^4$ theory in three spatial dimensions. The transition is induced by a time-dependent temperature drop in the heat bath to which the fields are coupled. We present a detailed account of the dynamics of the fields and vortex string formation as a function of the quench rate. The results are found in good agreement to the theory of defect formation proposed by Kibble and Zurek.Comment: 4 pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
126
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 133 publications
(137 citation statements)
references
References 19 publications
10
126
1
Order By: Relevance
“…The results show no evidence for the formation of topological defects at the anticipated levels, contrary to expectations based both on the old experiment [8], the theory * and the 3 He data [6,7]. * Although a factor f > ∼ 10 in the formula for the string density n ∼ 1/(fξ) 2 could explain the new results and seems consistent with recent numerical studies [10].…”
Section: Introductioncontrasting
confidence: 50%
See 3 more Smart Citations
“…The results show no evidence for the formation of topological defects at the anticipated levels, contrary to expectations based both on the old experiment [8], the theory * and the 3 He data [6,7]. * Although a factor f > ∼ 10 in the formula for the string density n ∼ 1/(fξ) 2 could explain the new results and seems consistent with recent numerical studies [10].…”
Section: Introductioncontrasting
confidence: 50%
“…Below T c , on the other hand strings are exponentially suppressed and only those smaller than the temperature dependent length l ≃ T /σ eff (T ) are likely as thermal fluctuations. It is the existence of long strings as thermal fluctuations that will lead to defect formation if the system is suddenly cooled [10]. Although some of the above comments may seem somewhat marginal they establish that the thermodynamics of the U (1) theory under consideration is much richer than the assumptions on which the traditional role of the Ginzburg regime is based.…”
Section: Fig 1 the Dependence Of The Thermal Distribution Of Vortexmentioning
confidence: 87%
See 2 more Smart Citations
“…Computational simulations as well as numerical studies have confirmed the exponents given in both scaling laws [6,7]. The latter scaling exponent relating to defect annihilation has been confirmed experimentally -also using liquid crystals [8,9].…”
supporting
confidence: 53%